The mutability and ambiguity of the wind. What art for a quasi-thing? (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Perhaps no meteorological phenomenon has enjoyed more interest than the wind. Both mutable and ambiguous, it has been interpreted in many ways over the centuries. This is particularly evident in the graphic arts, which have employed different strategies of representation.Taking the neo-phenomenological interpretation of the wind as a ‘quasi-thing’, this paper explores the most common ways of representing this particular phenomenon within the European iconographic tradition, with the aim of identifying those that can best depict it in its quasi-thingly nature. More specifically, this work aims to show that – under certain conditions – painting is not only able to express the particular meteorological and affective nature of the wind, but can also be a useful tool for shedding light on the so-called theory of atmospheres, which are themselves grounded in the thesis of the spatiality of feelings.With the help of a few examples from modern and contemporary painting, in which the wind finds its place as an aesthetic phenomenon, this paper outlines the possible characteristics of an atmospheric art in which the phenomenon is represented in all its affective power. Such art discloses or emphasizes the affective influence that phenomena such as the wind can exert on us, radically altering our sensory relationship with the world.